DESA PARIWISATA BERORIENTASI SEBAGAI PENGEMBANGAN WILAYAH PERKOTAAN DENGAN PENDEKATAN HYBRID SPACE - Pradipto, Eugenius; Prakoso, Aditha Agung; Wulansari, Maria Ariadne Dewi; Fadhilla, Titania Nur (Universitas Aisyiyah Yogyakarta, 2020)
Abstract: Sudimoro Village is one of the villages that suffered from the eruption of Mount Merapi in October 2010. Over time, Sudimoro has become a potential space to learn about disaster mitigation and about the use of bamboo as a sustainable building material. Geographically, Sudimoro is surrounded by many developing tourist destinations, in the west there are Elo Progo River Rafting and Mendut Temple, on the east side there is Gunungpring Cemetery. This village has the potential as a strategic Hybrid Space to connect all tourist points as tourist magnets, to support urban development. After 10 years, the temporary bamboo shelter in Sudimoro village began to be gradually developed by residents into a tourist village. Apart from preserving the historical value of the Bamboo Shelter and increasing the socio-cultural and local ecological values, the use of bamboo buildings is also a strategy for the sustainability of the Bamboo Shelter’s existence. In this paper, the author aims to make a comparison of the position of Sudimoro village compared to other tourist villages, as well as an assessment of Sudimoro's potential to become an urban tourism development area with the Hybrid Space approach.